2020
DOI: 10.1371/journal.pone.0230956
|View full text |Cite
|
Sign up to set email alerts
|

Basic self-disturbances are associated with Sense of Coherence in patients with psychotic disorders

Abstract: BackgroundThe Sense of Coherence (SOC) theory gives a possible explanation of how people can experience subjective good health despite severe illness. Basic self-disturbances (BSDs) are subtle non-psychotic disturbances that may destabilize the person's sense of self, identity, corporeality, and the overall 'grip' of the world. AimOur objective was to investigate associations between BSDs and SOC in patients with psychotic disorders. DesignThis is a cross-sectional study of 56 patients diagnosed with psychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is also unclear how helpful antipsychotics are for reducing self-disturbances (Nelson et al, 2021), which, as we have stressed, appear to be crucial to predicting the long-term trajectory of a psychotic episode (see Burgin et al, 2022, for a review). It was recently shown that reductions of self-presence were associated with a lower sense of coherence in people with schizophrenia and other psychotic disorders (Svendsen et al, 2020). Sense of coherence indicates a "subjective experience of good health," despite having a severe illness and is related to a sense of ability to manage the disorder and to feel that life has meaning (Svendsen et al, 2020).…”
Section: A Dopamine's Role In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…It is also unclear how helpful antipsychotics are for reducing self-disturbances (Nelson et al, 2021), which, as we have stressed, appear to be crucial to predicting the long-term trajectory of a psychotic episode (see Burgin et al, 2022, for a review). It was recently shown that reductions of self-presence were associated with a lower sense of coherence in people with schizophrenia and other psychotic disorders (Svendsen et al, 2020). Sense of coherence indicates a "subjective experience of good health," despite having a severe illness and is related to a sense of ability to manage the disorder and to feel that life has meaning (Svendsen et al, 2020).…”
Section: A Dopamine's Role In Schizophreniamentioning
confidence: 99%
“…It was recently shown that reductions of self-presence were associated with a lower sense of coherence in people with schizophrenia and other psychotic disorders (Svendsen et al, 2020). Sense of coherence indicates a "subjective experience of good health," despite having a severe illness and is related to a sense of ability to manage the disorder and to feel that life has meaning (Svendsen et al, 2020). As self-presence may not be affected by antipsychotic treatment, patients using antipsychotics might still feel that life is difficult to manage, even if positive symptoms are reduced.…”
Section: A Dopamine's Role In Schizophreniamentioning
confidence: 99%
“…The autistic need for self-consistency is reflected in the soul-searching quest many of us engage in prior to and following formal diagnosis (Brown et al, 2021;Corden et al, 2021;Dwyer, 2022;Leveto 2018;Sarrett, 2016), as well as the identity-questioning many experience (Yule, 2021). Self-consistency (in most contemporary literature, it is known as selfcoherence; Antonovsky, 1993;Eriksson & Mittelmark, 2017;Heine et al, 2006;Heintzelman et al, 2013;Martela & Steger, 2016;Stewart & Neimeyer, 2001;Svendsen et al, 2020), however, is a general need reflected in the human desire to understand oneself and one's perceptions. It appears to be cross-culturally stable for ND and NT persons alike (Church et al, 2012), linked to increased quality of and meaning in life (Eriksson & Lindström, 2007;Heine et al, 2006;Heintzelman et al, 2013;Martela & Steger, 2016;Pallant & Lae, 2002).…”
Section: Contact As Relational Activism For the Meeting Of Needsmentioning
confidence: 99%
“…Low baseline levels of basic self-disturbances and further reductions over time independently predict recovery [ 50 ]. Significant association between basic self-disturbances and sense of coherence, not mediated by other clinical symptoms, was reported, identifying high levels of basic self-disturbances as independent contributors to poor sense of coherence [ 51 ].…”
Section: Introductionmentioning
confidence: 99%